2019
DOI: 10.1680/jenge.15.00081
|View full text |Cite
|
Sign up to set email alerts
|

Acid rain intrusion effects on the compressibility behaviour of residual soils

Abstract: This paper presents the results of experiments designed to investigate the effect of acid rain on the compressibility behaviour of residual soils. Sedimentary residual soil (SRS) and igneous residual soil (IRS) with different mineral compositions were collected from two locations in Malaysia. The specimens were infiltrated by artificial acid rain (AAR) at varying pH values of 2, 3, 4, 5 and 5·6 and at different fluxes of 1, 5 and 20 years. At the end of each AAR flux interval, compressibility, zeta potential, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…Ambas imagens apresentam uma estrutura cristalina em camadas ou pacotes. Segundo Bakhshipour et al (2017), as estruturas cristalinas dos solos dispostas em camadas, constituídos principalmente por caulinita, ao interagirem com ácido sulfúrico, sofrem modificações e suas microestruturas tornam-se semelhantes a agulhas ou em formas de fibras. Tal evidência não foi verificada nas amostras de caulim, em ambos ensaios, as quais mantiveram o formato característico do mineral de origem após exposição ao ácido, como pode ser observado na Figura 2 (b).…”
Section: Amostraunclassified
“…Ambas imagens apresentam uma estrutura cristalina em camadas ou pacotes. Segundo Bakhshipour et al (2017), as estruturas cristalinas dos solos dispostas em camadas, constituídos principalmente por caulinita, ao interagirem com ácido sulfúrico, sofrem modificações e suas microestruturas tornam-se semelhantes a agulhas ou em formas de fibras. Tal evidência não foi verificada nas amostras de caulim, em ambos ensaios, as quais mantiveram o formato característico do mineral de origem após exposição ao ácido, como pode ser observado na Figura 2 (b).…”
Section: Amostraunclassified
“…However, the amount of dry-wet cycles was positively correlated with the expansion rate at the early times, then stabilizes at the late times, with a large increas after two epochs of action. Bakhshipour et al [12] studied the influence of acid rain intrusion on the compression performance of residual soil; Liu et al [13][14][15] found the uniaxial compressive strength, elastic modulus, cohesion, internal friction angle, and triaxial compressive strength decreased with the increase of dry-wet cycles. Liu and Gui [16] concluded that the shear strength and cohesion of montmorillonite-quartz sand remolded soil decreased due to the reaction of H + ion and montmorillonite under acidic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, acid rain would accelerate the precipitation of calcium ions in light soil and increase soil permeability [12]. As a result, the acid rain would destroy the soil structure, causing the loss of metal ions such as iron and aluminum from the soil matrix [13,14]. e lower the pH value of infiltration acid rain, the greater the compressibility of the soil.…”
Section: Introductionmentioning
confidence: 99%